2022
DOI: 10.1128/spectrum.02315-21
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoDrug Discovery Strategies Identified ADMET Properties of Decoquinate RMB041 and Its Potential Drug Targets against Mycobacterium tuberculosis

Abstract: This article elaborates on the mechanism of action of a novel antibiotic compound against both, active and dormant Mycobacterium tuberculosis and describes its pharmacokinetics (including oral bioavailability and toxicity). Information provided in this article serves useful during the search for drugs that shorten the treatment regimen for Tuberculosis and cause minimal adverse effects.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Our results also demonstrated that plumbagin has neither an inhibition nor a substrate profile with the main enzymes of the cytochrome P540 family. Cytochrome P450 is the main metabolic enzyme to be considered in the process of drug metabolism, which can oxidize xenobiotics to facilitate their elimination [ 56 ]. The inhibition of these enzymes suggests the potential for the occurrence of toxicity and possible interference with the pharmacokinetics of co-administered compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also demonstrated that plumbagin has neither an inhibition nor a substrate profile with the main enzymes of the cytochrome P540 family. Cytochrome P450 is the main metabolic enzyme to be considered in the process of drug metabolism, which can oxidize xenobiotics to facilitate their elimination [ 56 ]. The inhibition of these enzymes suggests the potential for the occurrence of toxicity and possible interference with the pharmacokinetics of co-administered compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Undesirable pharmacokinetics is one of the main reasons for the failure of drug development, therefore, essential evaluation needs to be undertaken during the discovery stage. Currently, ADME properties can be obtained through in silico methods [ 15 , 16 ], but the determination of drug exposure in plasma and target tissue remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating ADMET analysis is crucial for exploring the potential of the selected compounds from molecular docking [14]. ADMET analysis provides insights into a compound's pharmacokinetic properties and potential safety risks, aiding in identifying compounds with favorable ADMET profiles [15].…”
Section: Introductionmentioning
confidence: 99%